A Global Humanities Approach to the United Nations' Sustainable Development Goals Understanding Planet, People, and Prosperity - Comfort, Kelly (Routledge Taylor & Francis Group, 2024)
This edited textbook explores the 17 UN SDGs through 12 works from the humanities, including films, novels, and photographic collections. It provides students with the knowledge and understanding of how the humanities engage in broader social, political, economic, and environmental dialogue, offering a global perspective that crosses national and continental borders. The book takes students through the UN SDGs from a theoretical perspective through to practical applications, first through specific global humanities examples and then through students' own final projects and reflections. Centered around three major themes of planet, people, and prosperity, the textbook encourages students to explore and apply the Goals using a place-based, culturally rooted approach while simultaneously acknowledging and understanding their global importance. The text's examples range from documentary and feature film to photography and literature, including Wang Jiuliang's Plastic China, Kip Andersen and Keegan Kuhn's Cowspiracy: The Sustainability Secret, Barbara Dombrowski's Tropic Ice: Dialog Between Places Affected by Climate Change, and Aravind Adiga's The White Tiger, among others. Providing diverse geographic and cultural perspectives, the works take readers to Argentina, Australia, Bolivia, China, Costa Rica, Ecuador, France, Greenland, Haiti, India, Japan, Peru, Rwanda, Senegal, and the United States. This broad textbook can be used by students and instructors at undergraduate and postgraduate levels from any subject background, particularly, but not exclusively, those in the humanities. With added discussion questions, research assignments, writing prompts, and creative project ideas, students will gain a nuanced understanding of the interconnectivity between social, cultural, ethical, political, economic, and environmental factors.